Evaluation of the New Student Admission Website of STMIK Widya Cipta Dharma Using the End-User Computing Satisfaction Method - Damaya, Filio Angga; Pratiwi, Heny; Yunita, Y (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2025)
The New Student Admission (PMB) website is one of the platforms used in the admission and registration process for prospective students at STMIK Widya Cipta Dharma. An evaluation of the PMB website is necessary to ensure user convenience and satisfaction during the registration process. This study aims to evaluate the new student admission website of STMIK Widya Cipta Dharma using the End-User Computing Satisfaction (EUCS) method. The EUCS method consists of five main dimensions: content, accuracy, format, ease of use, and timeliness. Data was collected through questionnaires distributed to registered students, prospective students of STMIK Widya Cipta Dharma, and users of the PMB website. The analysis results indicate user satisfaction in using the PMB website.